Utility of massive open online courses (MOOCs) concerning outbreaks of emerging and reemerging diseases - Bendezu-Quispe, Guido (2017)
ABSTRACT The emergence and re-emergence of infectious diseases such as Ebola, chikungunya, and Zika increase the necessity of knowledgeable and skilled health professionals. Massive open online courses (MOOCs) arise as opportunities that allow people around the world to participate in higher education courses. A search was conducted on specialized MOOC platforms to find courses related to outbreaks, using terms included in the list of the WHO disease outbreaks from January 1st to December 31st, 2016. We found seven courses about Ebola, two about Zika, three about the dynamics of epidemics and pandemics, and only one course about dengue, chikungunya, and malaria. Most of the courses were conducted in English. The courses on Ebola, Zika and chikungunya were released after their last outbreak. MOOCs could be used to learn about health issues of global relevance, and with the necessity of fast divulgation of knowledge and skills. Translating the courses into more languages could give these courses more traction, and allow participation of professionals in regions affected by these outbreaks.